UBE4B interacts with the ITCH E3 ubiquitin ligase to induce Ku70 and c-FLIPL polyubiquitination and enhanced neuroblastoma apoptosis - Christophe Le Clorennec; Divya Subramonian; Yuchen Huo; Peter E. Zage (Cell Death and Disease, 2023)
Abstract Expression of the UBE4B ubiquitin ligase is strongly associated with neuroblastoma patient outcomes, but the functional roles of UBE4B in neuroblastoma pathogenesis are not known. We evaluated interactions of UBE4B with the E3 ubiquitin ligase ITCH/AIP4 and the effects of UBE4B expression on Ku70 and c-FLIPL ubiquitination and proteasomal degradation by co-immunoprecipitation and Western blots. We also evaluated the role of UBE4B in apoptosis induced by histone deacetylase (HDAC) inhibition using Western blots. UBE4B binding to ITCH was mediated by WW domains in the ITCH protein. ITCH activation led to ITCH-UBE4B complex formation and recruitment of Ku70 and c-FLIPL via ITCH WW domains, followed by Ku70 and c-FLIPL Lys48/Lys63 branched polyubiquitination and proteasomal degradation. HDAC inhibition induced Ku70 acetylation, leading to release of c-FLIPL and Bax from Ku70, increased Ku70 and c-FLIPL Lys48/Lys63 branched polyubiquitination via the ITCH-UBE4B complex, and induction of apoptosis. UBE4B depletion led to reduced polyubiquitination and increased levels of Ku70 and c-FLIPL and to reduced apoptosis induced by HDAC inhibition via stabilization of c-FLIPL and Ku70 and inhibition of caspase 8 activation. Our results have identified novel interactions and novel targets for UBE4B ubiquitin ligase activity and a direct role for the ITCH-UBE4B complex in responses of neuroblastoma cells to HDAC inhibition, suggesting that the ITCH-UBE4B complex plays a critical role in responses of neuroblastoma to therapy and identifying a potential mechanism underlying the association of UBE4B expression with neuroblastoma patient outcomes.